Femoro-Popliteal Artery Bypass Surgery With Autologous Great Saphenous Vein Graft: 1st Time Experience in Chittagong Medical College Hospital - Maruf, Mohammad Fazle; Islam, Samirul; Hossain, Nazmul; Quaium Chowdhury, Muhammad Abdul; Akter, Tahmina; Rahman, Mamunur (Journal of Chittagong Medical College Teachers’ Association, 2015)
Peripheral arterial disease affects with loss of limb if untreated. For decades, arterial bypass has been regarded as one of the trustworthy and effective methods for treatment of atherosclerosis in lower limbs. A 65 year old male patient was treated for a worsening short distance intermittent claudication in left calf muscle. Clinical examinations identified occlusion of the superficial femoral artery. Peripheral Angiogram (PAG) revealed popliteal artery had good calibre with distal run off. Left superficial femoral artery to popliteal artery bypass was performed on the patient with autologous reversed great saphenous venous conduit. Post operative course was uneventful. The pulses of the dorsalis pedis and posterir tibial arteries in left leg regained and remain strong. The Ankle Brachial Index (ABI) increased from 0.60 to 1.09. As far as arterial bypass in lower limb is concerned, the efficacy is usually not so desireable because of lack of vascular substitutes, insufficient availability of autologous vessels and also the scarcity of skilled vascular surgeon. Therefore, it becomes our long-lasting desire to find out a safe and endurable graft conduit and also to establish vascular surgery in a city where this type of surgery was absent previously. We have recently succeeded in performing femoro-popliteal bypass surgery in Chittagong Medical College Hospital (CMCH). Probably this was the first successful femoro-popliteal bypass surgery with autologous great saphenous venous conduit for chronic arterial occlusive disease of lower limb in this hospital. JCMCTA 2015 ; 26 (1) : 46-51